Археологические исследования в Салачике в 2008 г. - Ибрагимова, А.М.; Бекиров, Т.Ш. (Археологічні дослідження в Україні, 2009)
The paper presents a short description of a new architectural and archaeological complex Zincirli medrese situated in the suburbs of Bakhchisaray discovered in 2008. It was a bath-house of two parts containing 10 rooms (5 in the women’s part and 5 in the men’s one), and a kulkhan (a heating system). The structure existed from the middle of the 15th c. to the end of the 18th c.